Native Ligand Carbonization Renders Common Platinum Nanoparticles Highly Durable for Electrocatalytic Oxygen Reduction: Annealing Temperature Matters. Issue 26 (20th May 2022) - Li, Zhicheng; Zou, Jinxiang; Xi, Xiangyun; Fan, Pengshuo; Zhang, Yi; Peng, Ye; Banham, Dustin; Yang, Dong; Dong, Angang
Abstract: Current protocols for synthesizing monodisperse platinum (Pt) nanoparticles typically involve the use of hydrocarbon molecules as surface‐capping ligands. Using Pt nanoparticles as catalysts for the oxygen reduction reaction (ORR), however, these ligands must be removed to expose surface sites. Here, highly durable ORR catalysts are realized without ligand removal; instead, the native ligands are converted into ultrathin, conformal graphitic shells by simple thermal annealing. Strikingly, the annealing temperature is a critical factor dictating the ORR performance of Pt catalysts. Pt nanoparticles treated at 500 °C show a very poor ORR activity, whereas those annealed at 700 °C become highly active along with exceptional stability. In‐depth characterization reveals that thermal treatment from 500 to 700 °C gradually opens up the porosity in carbon shells through graphitization. Importantly, such graphitic‐shell‐coated Pt catalysts exhibit a superior ORR stability, largely retaining the activity after 20 000 cycles in a membrane electrode assembly. Moreover, this ligand carbonization strategy can be extended to modify commercial Pt/C catalysts with substantially enhanced stability. This work demonstrates the feasibility of boosting the ORR performance of common Pt nanoparticles by harnessing the native surface ligands, offering a robust approach of designing highly durable catalysts for proton‐exchange‐membrane fuel cells. Abstract : Native surface ligands (e.g., oleylamine and oleic acid) attached to Pt nanoparticles during synthesis can be directly converted into ultrathin, conformal graphitic shells upon thermal annealing, rendering common Pt particles highly stable catalysts for the oxygen reduction reaction. This in situ ligand carbonization strategy is general and can also be applied to improve the stability of commercial Pt/C catalysts.